2018
DOI: 10.1007/s11033-018-4282-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of association between interleukin-8 − 845 T/C and + 781 C/T polymorphisms with periodontitis disease among population from Western Iran

Abstract: Periodontitis is a chronic inflammatory disease that influences the protective tissues of teeth. IL-8, a member of the chemokine super-family, plays vital roles in the pathogenesis of periodontitis with activation and migration of neutrophils in inflammatory regions. The purpose of present study was to evaluate the association of interleukin-8 - 845 T/C and + 781 C/T polymorphisms with periodontitis in an Iranian population. A total of 65 patients with periodontitis including 18 patients with chronic periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…This is also consistent with the pro-osteoclastogenic activity of IL-6 [44] and the overall chemoattractant effects of IL-8 [45]. Nevertheless, although certain haplotypes of the IL-8 gene have been shown to significantly associate with susceptibility to chronic periodontitis [46,47], there remain contradictory reports on IL-8 levels in the gingival crevicular fluid of healthy and chronic periodontitis patients [48][49][50][51]. Furthermore, even if IL-8 levels may be relevant markers of chronic periodontitis, this does not entail that they are the most relevant targets for an anti-inflammatory strategy, which should mostly focus on blocking the farthest-reaching mediators, those biomolecules that are likely to control important down-stream effectors.…”
Section: Establishing a Traditionsupporting
confidence: 75%
“…This is also consistent with the pro-osteoclastogenic activity of IL-6 [44] and the overall chemoattractant effects of IL-8 [45]. Nevertheless, although certain haplotypes of the IL-8 gene have been shown to significantly associate with susceptibility to chronic periodontitis [46,47], there remain contradictory reports on IL-8 levels in the gingival crevicular fluid of healthy and chronic periodontitis patients [48][49][50][51]. Furthermore, even if IL-8 levels may be relevant markers of chronic periodontitis, this does not entail that they are the most relevant targets for an anti-inflammatory strategy, which should mostly focus on blocking the farthest-reaching mediators, those biomolecules that are likely to control important down-stream effectors.…”
Section: Establishing a Traditionsupporting
confidence: 75%
“…Two studies were done with periodontitis affected patients, analysing IL-8 polymorphisms association with the disease 16,19 . Two studies analysed periodontitis and type 1 or 2 diabetes mellitus association with IL-8 polymorphisms along with patients affected by periodontal pathologies 17,18 .…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…CXCR1 and CXCR2 genes and their polymorphisms were reported by four studies 18,24,36,39 . Twenty-two studies focused on IL-8 polymorphisms and their different variants findings 12,[17][18][19][20][21][22][23][25][26][27][28][30][31][32][33]37,40,41,[43][44][45] .…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…This cytokine activates the migration of neutrophils in inflammatory regions [68]. The IL-8 gene is located on chromosome 4q13-q21 [46,88]. Previous studies have shown the association of IL-8 SNPs with PD [45].…”
Section: Interleukinmentioning
confidence: 99%